Perspectives on imitation: From neuroscience to social science: Volume 2 Imitation, human development, and culture - Hurley, Susan; Chater, Nick (Cambridge MIT Press, 2005)
Imitation is not the low-level, cognitively undemanding behavior it is often assumed to be, but rather--along with language and the ability to understand other minds--one of a trio of related capacities that are fundamental to human mentality. In these landmark volumes, leading researchers across a range of disciplines provide a state-of-the-art view of imitation, integrating the latest findings and theories with reviews of seminal work, and revealing why imitation is a topic of such intense current scientific interest. Perspectives are drawn from neuroscience and brain imaging, animal and developmental psychology, primatology, ethology, philosophy, anthropology, media studies, economics, sociology, education, and law. These volumes provide a resource that makes this research accessible across disciplines and clarifies its importance for the social sciences and philosophy as well as for the cognitive sciences. As a further aid to cross-fertilization, each volume includes extensive interdisciplinary commentary and discussion. The first volume considers possible mechanisms of imitation, including discussion of mirror systems, ideomotor and common coding theories, and the possibility of "shared circuits" for control, imitation, and simulation, and then takes up imitation in animals, with illuminating comparisons to human imitation. The second volume focuses first on the roles of imitation in human development and in learning to understand the minds of others, and then on the broader social and cultural roles and functions of imitation, including discussions of meme theory and cultural evolution, and of the pervasive imitative tendencies of normal adults and their relevance for understanding the effects of the media on human behavior.